2017
DOI: 10.2967/jnumed.116.182311
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Precision in Optoacoustic Tomography for Preclinical Imaging in Living Subjects

Abstract: Optoacoustic tomography (OT) is now widely used in preclinical imaging; however, the precision (repeatability and reproducibility) of OT has yet to be determined. We used a commercial small-animal OT system. Measurements in stable phantoms were used to independently assess the impact of system variables on precision (using coefficient of variation, COV), including acquisition wavelength, rotational position, and frame averaging. Variables due to animal handling and physiology, such as anatomic placement and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
94
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(106 citation statements)
references
References 30 publications
12
94
0
Order By: Relevance
“…The inter-and intra-tumour CoV for the CAL R tumours due the re-positioning of the animal (Table S2) were >22.0±21.2% and >26.5±8.3%, respectively, for all the parameters (Hb, HbO 2 , HbT and sO 2 ), hence similar to those obtained for the study without re-positioning the animal (see Table S1), over a 75 minute period, apart from animal 4. This also suggests that anaesthesia is the main experimental factor that contributes for the temporal variability of the signal, as found by Joseph et al [44].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The inter-and intra-tumour CoV for the CAL R tumours due the re-positioning of the animal (Table S2) were >22.0±21.2% and >26.5±8.3%, respectively, for all the parameters (Hb, HbO 2 , HbT and sO 2 ), hence similar to those obtained for the study without re-positioning the animal (see Table S1), over a 75 minute period, apart from animal 4. This also suggests that anaesthesia is the main experimental factor that contributes for the temporal variability of the signal, as found by Joseph et al [44].…”
Section: Discussionsupporting
confidence: 69%
“…This reflects a high variation in the measured signal of each animal, expected due to the increasing trend in haemoglobin and blood sO 2 over time. Joseph et al (2017) [44] studied the repeatability and reproducibility of PAI with the same system as that used here in the left kidney and spleen of 8-12 week old mice (n=7), acquiring images over a period of 90 minutes, under isoflurane anaesthesia. The authors found a steady increasing trend in HbT and blood sO 2 over the 90 minute imaging acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…Nordsmark and Overgaard [46], while investigating the relationship between hypoxia and tumour control after radiotherapy, showed that oxygenation in tumours, measured using Eppendorf oxygen electrodes, was independent of total haemoglobin levels, obtained from a venous blood sample acquired before the treatment. Also, Joseph et al [47] found that a higher coefficient of variation (CoV) was expected for haemoglobin than for sO 2 over either short periods of time (hours) or longer ones (days), as we have confirmed in a previous study [48]. This higher CoV makes Hb, HbO 2 and HbT less predictive parameters than blood sO 2 .…”
Section: Rtsupporting
confidence: 78%
“…47 For all the measurements, the phantoms were maintained at 34°C inside the . CC-BY-NC-ND 4.0 International license peer-reviewed) is the author/funder.…”
Section: Photoacoustic Tomography (Pat) Measurements and Calculationsmentioning
confidence: 99%
“…47 All the reagents for phantoms fabrication were purchased from Sigma Aldrich (Sigma-Aldrich Co.) unless otherwise stated. The DNA nanostructures were suspended inside sealed thin walled plastic tubes (0.3 cm diameter) that were placed at the center of the cylindrical phantoms (2 cm diameter) as shown in Figure S10b.…”
Section: Photoacoustic Tomography (Pat) Measurements and Calculationsmentioning
confidence: 99%